Binding body and self in visuo‐vestibular conflicts. (30th December 2014) - Macauda, Gianluca; Bertolini, Giovanni; Palla, Antonella; Straumann, Dominik; Brugger, Peter; Lenggenhager, Bigna
Abstract: Maintenance of the bodily self relies on the accurate integration of multisensory inputs in which visuo‐vestibular cue integration is thought to play an essential role. Here, we tested in healthy volunteers how conflicting visuo‐vestibular bodily input might impact on body self‐coherence in a full body illusion set‐up. Natural passive vestibular stimulation was provided on a motion platform, while visual input was manipulated using virtual reality equipment. Explicit (questionnaire) and implicit (skin temperature) measures were employed to assess illusory self‐identification with either a mannequin or a control object. Questionnaire results pointed to a relatively small illusion, but hand skin temperature, plausibly an index of illusory body ownership, showed the predicted drop specifically in the condition when participants saw the mannequin moving in congruence with them. We argue that this implicit measure was accessible to visuo‐vestibular modulation of the sense of self, possibly mediated by shared neural processes in the insula involved in vestibular and interoceptive signalling, thermoregulation and multisensory integration. Abstract : Vestibular signaling and its multisensory integration are crucial for the sense of a bodily self. Here we showed that moving on a motion platform congruently with a mannequin seen from a first person perspective cools down skin temperature. This suggests that conflicting visuo‐vestibular input alters thermoregulation as an implicit measure of body ownership.